INNOVATIVE TECHNOLOGIES OF CALVES REARING IN DAIRY CATTLE BREEDING - Semenov, V.G.; Baimukanov, D.A.; Alentayev, A.S.; Kirillov, N.K.; Karynbayev, A.K.; Aldyakov, A.V. (Scientific Journal of Pedagogy and Economics, 2020)
For the first time, the rationale of using polystim in the technology of calf rearing in private subsidiary plots, on small and medium farms has been scientifically substantiated and experimentally proved to activate the protective and adaptive functions of the body to the keeping conditions and to more fully realize the biological potential of resistance and productivity. Thus, live weight, average daily gain and growth rate of young cattle of the experimental group were higher by the end of the observation period (180 days) than in the control group: in the conditions of personal subsidiary plots by 6.6 kg, 33.3 g and 0.28, on small farms - by 5.2 kg, 20.0 g and 0.08, and with the technology of keeping on a medium farm - by 4.8 kg, 13.3 g and 0.23 (P<0.05 ) respectively. The dynamics of exterior measurements of animals of all groups were similar to the nature of changes in their live weight and their average daily gain. At the same time, the incidence of respiratory organs diseases and the gastrointestinal tract in newborn calves was reduced to 25-40%, the duration of the disease was reduced by 2.45; 1.31 and 1.93 days (P<0.05-0.001).